A symbolic interactionism perspective of using social media for personal and business communication. (April 2020) - Chen, Renee Rui; Davison, Robert M.; Ou, Carol Xiaojuan
Highlights: We attempt to understand how customers interpret the use of social media for personal and business communication and how customers respond to messages received. WeChat personal accounts and Moon Struck's official account offer radically different meanings to customers. WeChat personal accounts symbolizes a sociality-oriented meaning (e.g., relationship and image building). WeChat official accounts symbolizes information broadcasting-related meaning (e.g., selling, advertising, and branding). Both technological features and the distance of relationships among users contribute to the constructed symbolic meaning of technology, subsequently affecting use patterns. Abstract: Achieving the anticipated business benefits of a social medium is important as organizations diligently invest in different social media platforms. While much previous research assumes that social media helps organizations to communicate with customers, less is known about whether customers embrace using social media to interact with organizations. It is important to understand the role of social media for business communication from the customers' perspective, as this may significantly deviate from the organizations' own communicative intentions. In this exploratory case study of the Moon Struck hotel in China, we investigate both how customers interpret the hotel's use of WeChat official account for business communication and how customers respond to messages received from Moon Struck's WeChat account. Adopting a symbolic interactionism perspective, we surprisingly find that WeChat personal accounts and Moon Struck's official account offer radically different meanings to followers. Specifically, WeChat personal account symbolizes a sociality-oriented meaning (e.g., relationship and image building), while Moon Struck's WeChat official account symbolizes information broadcasting-related meaning (e.g., selling, advertising, and branding). Both technological features and the distance of relationships among users contribute to the constructed symbolic meaning of technology, subsequently affecting users' WeChat use patterns. The theoretical implications of this study are discussed and recommendations are made for future research and practice.